Ecología y distribución de Phragmipedium spp y Catasetum spp (Orchidaceae) en la cuenca alta del Ahuashiyacu, Cordillera Escalera, región San Martín, Perú - Huatangare Córdova, Esley (2000)
The present research work. Ecology and distribution of Phragmipedium spp. and Catasetum spp. in the upper basin of Ahuasbiyacu river, Cordillera Escalera Mountains, San Martín, Peru, was developed inside the geographic borders of Banda de Shilcayo district, ín the upper part of Ahuashiyacu river, Cordillera Escalera Mountains, San Martín province, Region San Martín, Peru. The studied area is located at altitudes between 600 and 1400 m. The objectives of this work are: doing a preliminary inventory of orchid species at Cordillera Escalera, studying the habitats of Phragmipedium and Catasetum, and the their asrociated species of Phragmipedíum boissierianum (Reichb.f.) Rolfe y Catasetum pusillum Scheinf. Additional objectives were to study general aspects of the floral biology of this species and to study the limitant factors that affect the life and pem1anence of species of Phragmipedium and Catasetum. In order to achieve the before mentioned goals I choosed to search .the upper Ahuashiyacu basin in a •1O month period of continuous evaluation in key sectors, where the h3.bitirt of the studied species occur. This research helps to answer sorne questions like: what species of ORCHIDACEAE can occur in the upper Ahuashiyacu basin after a severe deforestation impact on the forest? What species of Phragmipedium still occur in relation to the ones collected before and identified by David Bennett and Marco Leon?. The results of my investigations are: In the upper Ahuashiyacu Basin ecosystem actually occur reduced populations of Phragmipedium boissierianum (Reichb.f .) Rolfe, P. richteri Gruss, Catasetum pusillum Schweinf., C. saccatum Christ., C. peruvianum Dodson & Be!Ulett, and other 54 orchid specíes. The habitats of Pliragmipedium boissierianum (Reichb.f.) Rolfe and P. richteri Giuss are disturbed places as wet cliff roadsides, old lands lides and rocky places near streams. Both species are terrestrial, growing in a sandy soil pH=5.6 and 2,98% of organic matter. Only P. boissierianum (Reichb.f.) Rolfe had been found as epiphytes (on Cyathea sp.) or litophytes. The associated species of P. boissierianum (Reichb.f) Rolfe are P. richteri Gruss; Sobralia rosea Poepp & Endl. S. yauaperyesis Barb. Rodr.; BleJia catenulata Ruiz & Pav., and Prescottia tenuis Lindl. P.boissieriam1m (Reichb.f.) Rolfe is distributed in 3 sectors or biotopes:The tunnel, Cataratas de Ahuashiyacu and Maronilla. The flowering periods we distributed throughout the year in the following sequence: Pre flowering from February to May, Flowering from May to September, fruit development from July to October, seed dispersal from July to early November. During the flowering period P. boissierianum (Reichb.f.)Rolfe their flowers are visited by hwnmíngbirds and moths during daytime but. Observed that insects pollinate this species during night. A probable pollinazator is the beetle Pyroporus sp. (Coleoptera: Elateridae) Catasetum species inhabit primary and secondary forests. C. saccatum Christ. and C. peruvianum Dodson & Bennett are epiphytes on Protium sp. Pouteria sp. host trees. C. pusillum Schweinf is terrestrial, growing in white sand pH= 4.92 and 3.8% of organic matter. The associated species are E. secundum Jacq., C/eistes rosea Lindl., Cleistes vargasi Schweinf. Pre-Flowering of C. pusülum Schweinf. occur between February and April, Flowering occurs in April, fruit development from May to October, and seed dispersal in October. During Prefloweríng and Flowering periods, plants are visited by insects líke Hectatoma sp (ants), grassshoper ( Tettigonidae). It has been observed that C. pusülum Schweinf. is pollinated by Euglossa :sp. Factors affecting the survival of Phragmipedium and Catasetum species m upper Ahuashiyacu basin are: Tree slash and bum for agriculture, fuelwood and timber co11ection, cleaning roadsides for maintenance, selective extraction, burning grasslands, dispensing of trash and toxic waste, diseases present in natural populations of P. boissierianum (Reichb.f.) Rolfe (caused by Fu:sarium sp.), and C.pusillum Schweínf. (caused by Gloeosporium sp.). As a result of the mentioned factors we have a important conclusion: the probable extinctíon and disappearing of Phragmipedium besseae Dodson & Kuhn from its habitats. Additionally all the species in the studied area are in danger of extintion. For this reason it is very important to preserve them using for example micropropagation for reintroduction. It is necessary to develop a project far orchid production and trade including local farmers, or other projects considered important. Additionally it is necessary to ha.ve strict policies for avoiding trade of wild collected species, according to national an intemational laws and treaties that protects biodiversity.